2019
DOI: 10.1615/specialtopicsrevporousmedia.2018027168
|View full text |Cite
|
Sign up to set email alerts
|

Nanofluid Transport in Porous Media: A Review

Abstract: Convection heat transfer mode is the principal topic in thermal transfer. So, it is the matter of many numerical and experimental studies. In recent years, much attention was given to the use of free/forced/mixed convection heat transfer with nanofluids in geothermal engineering, storage of radioactive nuclear waste, solar collectors, transpiration cooling, performance of cold storage, separation processes in chemical industries, thermal insulation of buildings, filtration, space technology, transport processe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 76 publications
0
25
0
Order By: Relevance
“…When > 0 , the surface of the body is maintained at variable wall temperature T w (x) such that T w > T ∞ everywhere and surface volume fraction is maintained at constant value w such that w > ∞ . The geometric configuration function r * (x) is given as and acceleration due to gravity, which is a function of geometry of the body, is given as Using the boundary layer and Boussinesq approximations, the governing equations are represented by a system of coupled nonlinear PDEs and are defined as (1)(2)(3)(4) [14]:…”
Section: Physical Model and Governing Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…When > 0 , the surface of the body is maintained at variable wall temperature T w (x) such that T w > T ∞ everywhere and surface volume fraction is maintained at constant value w such that w > ∞ . The geometric configuration function r * (x) is given as and acceleration due to gravity, which is a function of geometry of the body, is given as Using the boundary layer and Boussinesq approximations, the governing equations are represented by a system of coupled nonlinear PDEs and are defined as (1)(2)(3)(4) [14]:…”
Section: Physical Model and Governing Equationsmentioning
confidence: 99%
“…In fact, lately the nanofluid technology has made an appearance as a new technique to enhance the heat transfer. A review of the application of the nanofluid transport is given in Menni et al [1]. Sheremet et al [2] worked on the unsteady free convection heat transfer characteristics of nanofluid using the mathematical nanofluid model proposed by Buongiorno.…”
Section: Introductionmentioning
confidence: 99%
“…on the nanofluids heat transfers. Furthermore, recent researchers [79][80][81][82][83][84][85][86][87][88] reviewed the nanofluids behavior in porous media, complex geometries, solar collectors, different channels and in different base fluids which is summarized efficiently for the researchers.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these studies were performed for conventional fluid heat-exchangers, where a higher performance was recorded compared to the case without a porous medium. On the other hand, nanofluidic fluxes are modeled in the presence of the porous media [5]. The effect of the thermal and mechanical properties of the fluid, as well as the characteristics of the porous medium, have been the subject of studies, which have shown the effectiveness of combining the two techniques together, i.e.…”
Section: Introductionmentioning
confidence: 99%